Mechanical Ventilation Management for Aneurysmal Subarachnoid Hemorrhage in ICU Settings: A Literature Review - Jacoeb, Joseph Ivan; Bernadus Realino Harjanto; Tommy Nugroho Tanumihardja; Joshua Kurniawan; William Gilbert Satyanegara (Journal of Anesthesiology and Clinical Research, 2023)
Aneurysmal Subarachnoid Hemorrhage (aSAH) is one of the challenging neurologic emergencies with a high mortality rate along with various permanent disabilities. In order to provide the patient with the most appropriate and accurate treatment, as well as to prevent further complications, a multidiscipline approach is required. This study aimed to review the various mechanisms, indications, management, and sedation of mechanical ventilation in aSAH, along with a review of prone positioning and acute respiratory distress management in aSAH. Although the main injured organ is the brain, aSAH also affects the respiratory system through various mechanisms. The usage of mechanical ventilation plays an important part in brain oxygenation and perfusion and helps prevent related complications. Levels of oxygen and carbon dioxide in the blood might play some roles in aSAH patients. No significant difference was found in using various sedative regimens. Prone positioning is indeed beneficial for the oxygenation of aSAH patients, provided that continuous monitoring is done. Blood glucose and calcium levels might be able to help predict the outcome of aSAH patients. Mechanical ventilation plays an important part in aSAH management. Clinicians must be aware of the impact of mechanical ventilation on neurological organs and the cardiopulmonary system. Balancing between oxygenation, ventilation, and sedation must be in line with aSAH condition. Several prognostic factors and tools can help predict aSAH mortality that might be able to help the clinician tailor aSAH management to their patient's needs.